Lymph Node Fibroblastic Reticular Cells Attenuate Immune Responses Through Induction of Tolerogenic Macrophages at Early Stage of Transplantation. Issue 1 (8th December 2022) - Liu, Beichen; Liu, Huihui; Liu, Siwei; Qin, Chenchen; He, Xiaoya; Song, Zhengyang; Dong, Yujun; Ren, Hanyun
Abstract : Background: Fibroblastic reticular cells (FRCs) are a type of stromal cells located in the T zone in secondary lymphoid organs. Previous studies showed that FRCs possess the potential to promote myeloid differentiation. We aim to investigate whether FRCs in lymph nodes (LNs) could induce tolerogenic macrophage generation and further influence T-cell immunity at an early stage of allogeneic hematopoietic stem cell transplantation (allo-HSCT). Methods: LNs were assayed to confirm the existence of proliferating macrophages after allo-HSCT. Ex vivo—expanded FRCs and bone marrow cells were cocultured to verify the generation of macrophages. Real-time quantitative PCR and ELISA assays were performed to observe the cytokines expressed by FRC. Transcriptome sequencing was performed to compare the difference between FRC-induced macrophages (FMs) and conventional macrophages. Mixed lymphocyte reaction and the utilization of FMs in acute graft-versus-host disease (aGVHD) mice were used to test the inhibitory function of FMs in T-cell immunity in vitro and in vivo. Results: We found a large number of proliferating macrophages near FRCs in LNs with tolerogenic phenotype under allo-HSCT conditions. Neutralizing anti–macrophage colony-stimulating factor receptor antibody abolished FMs generation in vitro. Phenotypic analysis and transcriptome sequencing suggested FMs possessed immunoinhibitory function. Mixed lymphocyte reaction proved that FMs could inhibit T-cell activation and differentiation toward Th1/Tc1 cells. Injection of FMs in aGVHD mice effectively attenuated aGVHD severity and mortality. Conclusions: This study has revealed a novel mechanism of immune regulation through the generation of FRC-induced tolerogenic macrophages in LNs at an early stage of allo-HSCT. Abstract :